Linearization of 5G dual-band power amplifiers - Ahmed, Majid Faroug Eltayeb (2024)
A Master of Science thesis in Electrical Engineering by Majid Faroug Eltayeb Ahmed entitled, “Linearization of 5G dual-band power amplifiers”, submitted in December 2024. Thesis advisor is Dr. Oualid Hammi. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).